COMMUNITY MENTAL HEALTH IN PESHAWAR, THE NEED TO REFORM - Afridi, Shahid Khan; Minas, Harry; Afridi, Naseem Khan; Fatima, Shireen; Chopra, Prem (Journal of Ayub Medical College Abbottabad, 2010)
Community mental health is a neglected field in many developing countries including Pakistan. Common mental disorders are high in prevalence, particularly in women. Community mental health services are lacking in Peshawar, which faces a number of challenges owing to sociopolitical instability. The aim of this literature review is to evaluate and interpret current research relevant to community mental health reform, including a review of the evidence regarding community mental health service. A selected review of published literature was undertaken using the PubMed, PsychINFO and Cochrane Database of Systematic Reviews databases. The intervention studies included in this review demonstrate that community based mental health services closely aligned with primary care services have the potential to facilitate improvements in access to care and also improvements in mental health outcomes. It concludes that lack of proper mental health policy and non-integration of mental health in primary health care adversely affects the outcome of mental health progress in community.